Integrating Subak Local Wisdom to Enhance Sustainable Agricultural Entrepreneurship and Economic Development in Tolai Village - Wilau, Selda; Guampe, Feliks Arfid; Kayupa, Olvit Olniwati (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study explores the integration of local wisdom, specifically the Subak system, into sustainable agricultural entrepreneurship in Tolai Village, Torue District, Parigi Moutong Regency. Subak, a traditional Balinese irrigation system, incorporates the principles of Tri Hita Karana, which emphasizes harmony between humans, nature, and spirituality. The research examines how Subak practices, combined with modern agricultural techniques, promote ecological sustainability, enhance agricultural productivity, and strengthen community cohesion. The study also discusses the challenges faced by Subak, such as irrigation infrastructure issues, climate change, and pest management, and highlights adaptive strategies implemented by local farmers. Furthermore, the study underscores the importance of knowledge transfer to younger generations to ensure the continuity of Subak and its practices. The findings suggest that the integration of local wisdom into agricultural entrepreneurship contributes to the preservation of cultural heritage, supports food security, and fosters socio-economic resilience in rural communities.